Gus Dur and the Deliverance of Meutya Hafid and Budiyanto in 2005: the Role of Legitimacy Issues in Negotiating with Armed Group - Husni Mubarok; Yandry Kurniawan (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to analyze the role of an individual actor in hostage negotiation using legitimacy issues and a deductive-qualitative research approach. These research methods are closely related to the interpretation of quality or narrative, which cannot be described with numbers or values. A deductive approach was taken to conclude the research data that the authors found through the data findings. In this case, a negotiator (mediator) for releasing a hostage is a communicator, and a capable communicator will send the message effectively and efficiently. A negotiator is also an analyst who must read the hostage situation and conditions, especially knowing the characteristics of the hostage-takers. Specifically, legitimacy is one of the factors that a hostage release negotiator must own. Communication skills can support this factor. To achieve this, a negotiator ultimately should have the skills of interpersonal communication and intercultural communication. Gus Dur’s legitimacy factor played an essential role in the diplomacy and negotiation process, especially in this hostage case. Therefore, this study explores why an individual actor successfully overcame this hostage crisis. The role of the former Indonesian President, K.H. Abdurrahman Wahid (Gus Dur), as a concrete example of the success of an individual actor in hostage negotiation, was determined by his legitimacy.